"What's Past Is Prologue": A Framework, Review, and Future Directions for Organizational Research on Imprinting. (January 2015) - Simsek, Zeki; Fox, Brian Curtis; Heavey, Ciaran
Organizational researchers have long used imprinting as a theoretical lens for a historically embedded understanding of diverse, significant phenomena for explanatory, evaluative, and managerial purposes. The intuitive appeal of imprinting has facilitated its widespread diffusion throughout numerous disciplines and research fields, but the growing fragmentation of associated theory and evidence has blurred our understanding of the nature, sources, and mechanisms of imprinting as well as the context in which imprinting shapes the behavior and outcomes of distinct entities. To address these issues, we begin by developing a framework for generalizing theoretical constructs, statements, and relationships across levels of analysis, contexts, and disciplinary boundaries. Using the core themes of this framework, we next provide a systematic review of 119 imprinting studies allowing for more definitive statements about what we know, do not know, and should know about imprinting. Finally, by building on the review, together with the proposed framework, we chart a focused course for future inquiry and applications for organizational research on imprinting.